Sensory and attention abnormalities in autistic spectrum disorders - Liss, Miriam; Saulnier, Celine; Fein, Deborah; Kinsbourne, Marcel (Autism : the international journal of research and practice, 2006)
Individuals with autistic spectrum disorders (ASDs) often experience, describe and exhibit unusual patterns of sensation and attention. These anomalies have been hypothesized to result from overarousal and consequent overfocused attention. Parents of individuals with ASD rated items in three domains, ‘sensory overreactivity’, ‘sensory underreactivity’ and ‘sensory seeking behaviors’, of an expanded version of the Sensory Profile, a 103-item rating scale developed for the present study. Parents also rated symptom severity, overselective attention and exceptional memory, and completed the Vineland Adaptive Behavior Scales. Of 222 rated subjects, 144 had complete data. Cluster analysis showed the predicted overfocused pattern of sensation and attention, comprising overreactivity, perseverative behavior and interests, overfocused attention and exceptional memory in 43 percent of this sample. This pattern was striking in 10 percent. The neurological basis of overreactivity and overfocusing is discussed in relation to the overarousal hypothesis. Attention is drawn to its considerable prevalence in the ASD population.